Patterns of Use of Flexible Sigmidoscopy, Colonoscopy and Gastroscopy: A Population-Based Study in a Canadian Province - Robert J Hilsden (Canadian Journal of Gastroenterology)
BACKGROUND & AIMS: Flexible sigmoidoscopy, colonoscopy and gastroscopy are important in the diagnosis and treatment of gastrointestinal (GI) diseases. Pressure on endoscopy resources is expected due to increased screening for GI cancers. The present study examined patterns of use of GI endoscopy in a Canadian province, Alberta, with universal health care insurance.